Droughts preceding tree mortality events have increased in duration and intensity, especially in dry biomes - Antonio Gazol; Manuel Pizarro; William M. Hammond; Craig D. Allen; J. Julio Camarero (Nature Communications)
Abstract The thresholds of drought duration and intensity required to provoke pulses of tree mortality across Earth’s biomes remain unclear. Using globally-extensive updated databases of drought-associated tree mortality, we report substantial diversity in the types of drought events that cause tree death in different forest types. Tree-killing droughts are longer, more intense and have higher completeness (proportion of extreme drought within long-lasting droughts) in dry versus wet biomes. Mortality-inducing droughts are more intense and show higher completeness in angiosperm-dominated forests. We find a marked tendency towards long-lasting and more severe and complete droughts in recent years, particularly in more arid sites. Warming-amplified aridity is a main factor underpinning these variations. Differences in “sampling effort” across regions make it challenging to characterize the high variability in drought-induced tree mortality events. In this work we demonstrate the need to create, continuously update, and refine more extensive field-based tree mortality monitoring programs globally.